Sociological Dimensions of the Application of Islamic Inheritance in Indonesia - Syabbul Bachri; Roibin Roibin; Ramadhita Ramadhita (Justicia Islamica, 2024)
Differences in place and time, shifting conditions and situations, and societal changes cannot be avoided. However, there is a view that Islamic inheritance law is specific and fixed so that it cannot be modified. This study examines the application of inheritance law using the perspective of double movement theory by looking at the sociological dimensions that developed in Indonesia. This research is a sociological, legal research using qualitative data. The approach used in this research is socio-historical, intended to determine generalizations based on specific historical facts related to the application of Islamic inheritance law. The collected data is identified and verified, then analyzed using Fazlur Rahman's double movement theory. The results showed that based on moral ideals generalized based on double movement theory, it was found that justice and benefit became the primary reference in the application of Islamic inheritance law in Indonesia. Islamic inheritance law can flexibly adjust Indonesian society's environmental and social conditions. This research presents a methodological framework for a more adaptive and flexible application of Islamic inheritance law in line with Indonesia's diverse cultural landscape and evolving social norms.